2013
DOI: 10.1371/journal.pone.0079907
|View full text |Cite
|
Sign up to set email alerts
|

λ Phage Nanobioparticle Expressing Apoptin Efficiently Suppress Human Breast Carcinoma Tumor Growth In Vivo

Abstract: Using phages is a novel field of cancer therapy and phage nanobioparticles (NBPs) such as λ phage could be modified to deliver and express genetic cassettes into eukaryotic cells safely in contrast with animal viruses. Apoptin, a protein from chicken anemia virus (CAV) has the ability to specifically induce apoptosis only in carcinoma cells. We presented a safe method of breast tumor therapy via the apoptin expressing λ NBPs. Here, we constructed a λ ZAP-CMV-apoptin recombinant NBP and investigated the effecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 40 publications
1
14
0
Order By: Relevance
“…However, Apoptin has been shown to be able to induce the apoptosis in a variety of tumor cells [18], [18] and efficient delivery systems is are required to transfer Apoptin to cancer cells. Here we showed that the ability of BV-displaying anti-HER2 scFv to deliver Apoptin into breast cancer cells was demonstrated (Figure 7).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, Apoptin has been shown to be able to induce the apoptosis in a variety of tumor cells [18], [18] and efficient delivery systems is are required to transfer Apoptin to cancer cells. Here we showed that the ability of BV-displaying anti-HER2 scFv to deliver Apoptin into breast cancer cells was demonstrated (Figure 7).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported an antitumor effect of Apoptin in breast cancer cells. Shoae-Hassani and colleagues constructed a λ phage expressing the Apoptin which significantly inhibited growth of the various breast cancer cell lines in vitro [18]. AnoOther study also showed that HSA-mediated Apoptin infection was able to reduce the viability and induce the apoptosis in MCF-7 cells [41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…, March 2019, 25, 44-49 | 47 One of the most prominent features of CAV-Apoptin is its specific cytotoxicity in cancerous cells, as shown in many studies to date. [22][23][24] Despite extensive studies on CAV-Apoptin, HGV-Apoptin was discovered recently and its apoptotic effects has been evaluated on a few cell lines. In this study, we moved a step forward to show that HGV-Apoptin has cytotoxic effects on Non-small-cell lung carcinoma cell line A549, while it had no effects on non-cancerous human embryonic kidney cell line HEK-293.…”
Section: Figure 2 Transfection Efficiency Gfp Expression and In A549mentioning
confidence: 99%
“…Further, modified phage nanobioparticles (NBPs) such as k phage can safely deliver and express the transgene into eukaryotic cells. A recombinant NBP (k ZAP-CMVapoptin) could inhibit growth of breast carcinoma cell lines in vitro and in BT-474 human breast tumor in the nude mice model in vivo [199].…”
Section: Apoptinmentioning
confidence: 99%